A comparison of the dynamics of inflation in the USA and Japan: a VAR-VEC analysis. (2nd March 2015) - Fraccalvieri, Livia; Rosada, Mattia; Sironi, Emiliano
This paper examines inflation dynamics in the USA and Japan from 1980Q1 to 2013Q2. Changes in inflation, unemployment, output gap and policy interest rate behaviours during the last Great Recession that hit the US and Japanese economies are considered. According to a vector autoregression and VEC analyses, we found that even if there is evidence that inflation and unemployment are I (1), there is not a long–run inflation-unemployment tradeoff for the USA. Surprisingly, a short–run inflation-unemployment trade–off is very weak in Japan. This study is consistent with the opinion that the relationship between these two variables is not stable in either the short run nor in the long run: unemployment shows Granger causality with inflation but the opposite is not true in the USA. There is no Granger causality for Japan. We also find evidence that monetary policy lost its power in the US and Japanese real economies after the 2008 crisis.